102: Validation of a Vitamin D Dietary Intake Screening Questionnaire in Young Children. Issue 6 (1st June 2014) - Omand, J; Darling, PB; O'Connor, DL; Parkin, PC; Birken, CS; Lee, JG; Thorpe, KE; Maguire, JL
Abstract: BACKGROUND: Vitamin D dietary intake is an important predictor of vitamin D status in young children; however, measuring vitamin D intake in early childhood is challenging in the pediatric office setting. OBJECTIVES: To determine how well a simple, 1 min parent completed, dietary screening questionnaire (DSQ) completed in the pediatric office setting correlates with a detailed prospective three-day estimated food record (EFR) in measuring daily dietary vitamin D intake in children one to five years of age and to examine the correlation between the DSQ and EFR for assessing milk and vitamin D supplement intake. DESIGN/METHODS: The mean vitamin D dietary intake values derived from the DSQ and EFR were compared using a paired two-tailed Student's t test and Spearman correlation coefficient. RESULTS: Seventy-four children consented to participate in this study and were included in the analysis. Mean age was 34 months, 60% were male, 55% were European, and median zBMI was 0.12. The mean calorie intake according to the EFR was 1257 calories. The mean vitamin D dietary intake according to the DSQ was 493 (SD 399) IU and EFR was 443 (SD 389) IU. Paired student t-test revealed a P value of 0.37. The Spearman correlation was 0.47 for total vitamin D intake, 0.56 for vitamin D supplement intake and 0.69 for cow's milk intake. CONCLUSIONS: A 1 min DSQ completed in the pediatric office setting, including cow's milk and supplement use correlates well with a detailed EFR. Future studies include determining whether the DSQ predicts 25-hydroxyvitmain D.